2016
DOI: 10.1242/jeb.132860
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial physiology and reactive oxygen species production are altered by hypoxia acclimation in killifish (Fundulus heteroclitus)

Abstract: Many fish encounter hypoxia in their native environment, but the role of mitochondrial physiology in hypoxia acclimation and hypoxia tolerance is poorly understood. We investigated the effects of hypoxia acclimation on mitochondrial respiration, O 2 kinetics, emission of reactive oxygen species (ROS), and antioxidant capacity in the estuarine killifish (Fundulus heteroclitus). Killifish were acclimated to normoxia, constant hypoxia (5 kPa O 2 ) or intermittent diel cycles of nocturnal hypoxia (12 h:12 h normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 59 publications
7
55
2
Order By: Relevance
“…This suggests that inhibition of mitochondrial respiration rate contributes to metabolic depression with cold acclimation, and that this may be a key part of anoxia tolerance. Our results are also consistent with studies on isolated mitochondria from anoxic turtles (Bundgaard et al, 2018;Galli et al, 2013;Pamenter et al, 2016) as well as others on anoxia-tolerant animals exposed to hypoxia, such as frogs (St-Pierre et al, 2000b), killifish (Fundulus heteroclitus) (Du et al, 2016;Duerr and Podrabsky, 2010), epaulette sharks (Hemiscyllum ocellatum) and shovel-nosed rays (Aptychotrema rostrata) (Hickey et al, 2012). Inhibition of mitochondrial respiration rate is also central to the response to hypoxia in mammalian cells (Kim et al, 2006;Papandreou et al, 2006;Semenza, 2007).…”
Section: Resultssupporting
confidence: 92%
“…This suggests that inhibition of mitochondrial respiration rate contributes to metabolic depression with cold acclimation, and that this may be a key part of anoxia tolerance. Our results are also consistent with studies on isolated mitochondria from anoxic turtles (Bundgaard et al, 2018;Galli et al, 2013;Pamenter et al, 2016) as well as others on anoxia-tolerant animals exposed to hypoxia, such as frogs (St-Pierre et al, 2000b), killifish (Fundulus heteroclitus) (Du et al, 2016;Duerr and Podrabsky, 2010), epaulette sharks (Hemiscyllum ocellatum) and shovel-nosed rays (Aptychotrema rostrata) (Hickey et al, 2012). Inhibition of mitochondrial respiration rate is also central to the response to hypoxia in mammalian cells (Kim et al, 2006;Papandreou et al, 2006;Semenza, 2007).…”
Section: Resultssupporting
confidence: 92%
“…Among other ectothermic and endothermic vertebrate species, there are numerous examples of enhanced anaerobic performance in response to prolonged or repeated reliance on anaerobic metabolism, such as chronic and intermittent hypoxia and repeated sprint exercise (Hoppeler and Vogt, 2001;Pinder and Burggren, 1983) (Clanton and Klawitter, 2001) (Barnett et al, 2004;Borowiec et al, 2015;Du et al, 2016). These studies have demonstrated that many species have plasticity that improves physiological performance, either during or following the insult.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, structural and functional remodeling of the mitochondria has emerged as a critical component of hypoxic survival (24, 53, 55). Mitochondrial volume density has been observed to decrease with chronic hypoxia in a range of adult vertebrates, and this is often associated with large-scale reductions in ETC Complex activities and aerobic capacity (15, 21, 24, 25, 33, 34, 42, 55, 56). Mitochondrial efficiency can be improved by CIV subunit switching which maximizes the yield of ATP per oxygen molecule consumed and minimizes the production of harmful ROS (23).…”
mentioning
confidence: 99%